2018
DOI: 10.1002/tee.22780
|View full text |Cite
|
Sign up to set email alerts
|

An Area‐Efficient Resistor‐less On‐Chip Frequency Reference for Ultra‐Low Power Real‐Time Clock Application

Abstract: In this paper, we propose a fully integrated and area‐efficient resistor‐less relaxation oscillator (ROSC) for ultra‐low power real‐time clock (RTC) applications. The proposed ROSC is based on a conventional current‐mode ROSC and is modified to be an area‐efficient circuit configuration without using resistors. The proposed ROSC consists of a temperature‐compensated bias current generator (BCG), proportional to absolute temperature (PTAT) voltage source, current‐mode ROSC, shunt regulator, and output logic cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Several ELV circuit design techniques have been studied. [33][34][35][36][37][38][39][40][41][42] Matsuzuka et al reported an ELV ring oscillator (ROSC) using self-bias inverters (SBINVs) as a clock generator for the cold-start operation of a PMS. 33) The ROSC operated at an extremely low supply voltage of 42 mV.…”
Section: Introductionmentioning
confidence: 99%
“…Several ELV circuit design techniques have been studied. [33][34][35][36][37][38][39][40][41][42] Matsuzuka et al reported an ELV ring oscillator (ROSC) using self-bias inverters (SBINVs) as a clock generator for the cold-start operation of a PMS. 33) The ROSC operated at an extremely low supply voltage of 42 mV.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34][35] As a first step in the realization of such converters, an extremely low voltage oscillator is required to start the PMS. [32][33][34][35][36][37][38][39] A ring oscillator (ROSC) consisting of CMOS inverters is widely used because it can operate at lower supply voltages. However, the voltage gain of the inverter decreases as the supply voltage decreases, and thus it is difficult to operate at a sub-100 mV supply voltage, which is the typical output voltage range of a TEG with a small temperature difference.…”
Section: Introductionmentioning
confidence: 99%